Systematic Literature Review: The Effectiveness of the History of Science Approach in Improving Conceptual Understanding in Physics Education - Infa Damayanti; Lia Yuliati; Khusaini Khusaini (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
This study aims to analyze the effectiveness of the History of Science (HoS) approach in improving students' conceptual understanding in physics learning through the Systematic Literature Review (SLR) method using the PRISMA model. A total of six articles selected from 779 initial findings that met the inclusion and exclusion criteria were analyzed in depth. The synthesis results show that the HoS approach can strengthen conceptual understanding. The History of Science has been proven to help students overcome misconceptions, improve scientific reasoning skills, and enrich epistemological understanding of the nature of science. However, the SLR findings also confirm that empirical research on the implementation of HoS in the classroom is still limited, requiring the development of more structured learning strategies and improved teacher competencies to optimize the application of this approach in physics learning. Overall, this study confirms that HoS has great potential in supporting more meaningful, contextual, and conceptually oriented physics learning.